ИЖТИМОИЙ-ПЕДАГОГИК КОМПЕТЕНТЛИК БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ КАСБИЙ ТАЙЁРГАРЛИГИНИНГ МУҲИМ КОМПОНЕНТИ СИФАТИДА - Курбаниязова, З.К. (SCIENCE and SOCIETY, 2021)
The article reflects the scientific analysis of the development of socio-pedagogical competencies in future teachers, the relationship between professional acme and professional competence.